The Lasiocampidae (Lepidoptera: Lasiocampoidea) of Maputo Special Reserve, Mozambique: a provisional checklist with descriptions of three new species and taxonomic notes - Takano, Hitoshi; László, Gyula M. (Zootaxa, 2024)
A preliminary checklist of 39 species of lappet moths (Lasiocampidae) is provided for Maputo Special Reserve in southern Mozambique of which three are new to science, Diapalpus smithi sp. n., Eutricha giustii sp. n. and Rhinobombyx maputoensis sp. n., and a further ten are new country records. Several taxonomic changes are implemented in this paper: the synonymy of Sena prompta plusioides (Walker, 1862) syn. rev. with Sena prompta (Walker, 1855) is revived, Bombycopsis (Bufoidia) pallida Joannou & Krüger, 2009 syn. n. is synonymised with B. (B.) nigrovittata Aurivillius, 1927, and Lebeda mustelina Distant, 1899 is transferred to Leipoxais Holland, 1893 comb. n. Additionally, it is shown that the neotype designation by Zolotuhin & Gurkovich (2009) for Lebeda morosa Walker, 1865 is invalid although a new neotype is not selected as the original type may still be extant. All species, forms and both sexes where present are figured, as are the genitalia in the case of the new species and the comparative material examined.